Physiological and proteomic insights into melatonin-mediated delay in postharvest quality deterioration of blue honeysuckle fruit - Ruiling Liu; Lun Tao; Xiangjun Fang; Chaoyi Shen; Junwei Huo; Maratab Ali; Huizhi Chen; Hailong Yang; Haiyan Gao (Postharvest Biology and Technology, 2026)

1-Methylcyclopropene-mediated organic acid and sugar homeostasis enhances postharvest quality and shelf-life of fresh goji berry - Maratab Ali; Huizhi Chen; Weijie Wu; Ben Niu; Xiangjun Fang; Chaoyi Shen; Guannan Wang; Hangjun Chen; Ting Huang; Ming Yin; Ruiling Liu; Haiyan Gao (Food Chemistry, 2026)

Heterostructured nanocomposites with synergistic ROS-mediated antibacterial action and immune microenvironment remodeling for infected wound repair - Yujie Zhang; Ruiling Hu; Chengzhi Gao; Hang Wei; Jingyi Zhang; Xiaohui Ji; Shaobo Guo; Haibin Jiao (Chemical Engineering Journal, 2026)

Preparation and application of a sustained and unidirectional release active gelatin-sodium alginate/zein Janus film - Ben Niu; Yineng Liu; Ruiling Liu; Xiangjun Fang; Weijie Wu; Hangjun Chen; Chuan Tong; Huizhi Chen; Haiyan Gao (Food Hydrocolloids, 2026)

A dual-dynamic-bond network enabled, ultra-stretchable, and self-healing hydrogel for fresh produce damage prevention in postharvest logistics - Guannan Wang; Mengqi Zheng; Huizhi Chen; Ruiling Liu; Weijie Wu; Xiangjun Fang; Chaoyi Shen; Hangjun Chen; Haiyan Gao (Chemical Engineering Journal, 2026)

Investigation of the Degradation Mechanism of Dibutyl Phthalate in Soil Using Alkali-Modified Biochar and Persulfate Systems - Ruiling Zhang; Xinyu Zhang; Shuang Du; RuiRui Zhang; Jiayong Gao; Youjun Zhang; Jinpeng Liu (Water, Air, & Soil Pollution, 2026)

DCC and ADP modulate the disease progression in postharvest longan caused by Phomopsis longanae Chi in relation to ROS metabolism and cell wall integrity - Xiang Gao; Xiaoxuan Wang; Wenjing Lin; Huili Zhang; Ruiling Zhuo; Yihui Chen; Boqiang Li; Shiping Tian; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2026)

A Comparative Study on the Efficiency Process of Cellulosic Wastewater Fermentation by Oleaginous Yeasts - Shimiao Yao; Hailong Li; Ruiling Gao; Xuefang Chen; Can Wang; Lian Xiong; Xinde Chen (Indian Journal of Microbiology, 2026)

Unraveling the spatial chemical heterogeneity of Lentinula edodes: Integrative metabolomics and machine learning for cultivar and origin classification - Shenglong Lu; Chaoyi Shen; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Xiangjun Fang; Lishu Wang; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2026)

State-of-the-art insights into hydrogel innovations from structural engineering to smart preservation: Research trends and future directions - Yan Xu; Yiyi Cheng; Tao Yang; Huizhi Chen; Ben Niu; Xiangjun Fang; Weijie Wu; Chaoyi Shen; Guannan Wang; Bangdi Liu; Ruiling Liu; Haiyan Gao (Trends in Food Science & Technology, 2026)

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Ultraviolet-C treatment regulates the greening process of water bamboo (Zizania latifolia) shoots during postharvest storage - Xuening Zhao; Ruiling Liu; Yanchao Han; Ben Niu; Huizhi Chen; Xiangjun Fang; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2025)

The role of silica in biomass for calcium-modified biochar: Phosphorus removal mechanism and potential as a phosphate fertilizer application - Yongyi Chen; Ruiling Zhang; Jiayong Gao; Mujun Han; Songyan Qin; Kai Liu; Yajie Shu; Ruirui Zhang; Chang Shi; Yue Zheng (Journal of Environmental Sciences, 2025)

Hypothermal effects of cold anesthesia on the vitality and muscle quality of live Chinese mitten crab (Eriocheir sinensis) - Laixin Chen; Yanchao Han; Honglei Mu; Ben Niu; Ruiling Liu; Guannan Wang; Huizhi Chen; Lishu Wang; Hangjun Chen; Haiyan Gao (Food Research International, 2025)

Utilizing air discharge to preserve post-harvest quality of lotus root by suppressing fusarium oxysporum - Pengyue Zhang; Huizhi Chen; Ben Niu; Honglei Mu; Ruiling Liu; Yanchao Han; Ming Yin; Chaoyi Shen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

γ-Aminobutyric acid: An emerging biomolecule for maintaining the postharvest quality of fresh fruits and vegetables: A meta-analysis - Maratab Ali; Ben Niu; Weijie Wu; Akhtar Ali; Huizhi Chen; Ming Yin; Chaoyi Shen; Ruiling Liu; Haiyan Gao (Food Chemistry, 2025)

Salicylic acid nanoliposomes treatment alleviates chilling injury in postharvest baby ginger by regulating membrane lipid metabolism - Zhenzhen Mi; Honglei Mu; Yanchao Han; Ruiling Liu; Ben Niu; Guannan Wang; Huizhi Chen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Silk protein functionalized coatings and films as a novel biomaterial for fruit and vegetable preservation: current state and future prospects - Yan Wang; Weijie Wu; Ruiling Liu; Huizhi Chen; Haiyan Gao (Current Opinion in Food Science, 2025)

Effects of negative air ion treatment on postharvest storage quality and anthocyanin metabolism of grape - Chan Ma; Yanchao Han; Ruiling Liu; Ben Niu; Chaoyi Shen; Huizhi Chen; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2025)

Development of cushioning-antibacterial dual-functional cellulose packaging and its application for the Chinese bayberry during simulated transportation vibration - Yifan Xue; Ben Niu; Yanchao Han; Weijie Wu; Guannan Wang; Ming Yin; Xiangjun Fang; Ruiling Liu; Hangjun Chen; Haiyan Gao; Honglei Mu (Food Packaging and Shelf Life, 2025)

Composition and micromorphological determination of blue honeysuckle fruit (Lonicera caerulea L.) cuticular wax and its effects on fruit post-harvest quality - Ze Peng; Huizhi Chen; Ben Niu; Weijie Wu; Hangjun Chen; Mohamed A. Farag; Yifan Ding; Ruiling Liu; Haiyan Gao (Food Chemistry, 2025)

Shiitake mushroom-derived extracellular nanovesicles: Preparation, characterization, and inhibition of Caco-2 cells - Xueli Yang; Zihao Zong; Ben Niu; Hangjun Chen; Weijie Wu; Xiangjun Fang; Ruiling Liu; Haiyan Gao; Honglei Mu (Food Chemistry, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

Examining starch metabolism in lotus roots (Nelumbo nucifera Gaertn.) during post-harvest storage at different temperatures - Xinxin Gong; Ruiling Liu; Yanchao Han; Ben Niu; Weijie Wu; Huizhi Chen; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Food Chemistry, 2024)

Recent advances in Zizania latifolia : A comprehensive review on phytochemical, health benefits and applications that maximize its value - Weijie Wu; Yanchao Han; Ben Niu; Baiqi Yang; Ruiling Liu; Xiangjun Fang; Huizhi Chen; Shangyue Xiao; Mohamed A. Farag; Shiqi Zheng; Jianbo Xiao; Hangjun Chen; et al. (Critical Reviews in Food Science and Nutrition, 2024)

The dual function of calcium ion in fruit edible coating: Regulating polymer internal crosslinking state and improving fruit postharvest quality - Yiqin Zhang; Qi Kong; Ben Niu; Ruiling Liu; Huizhi Chen; Shangyue Xiao; Weijie Wu; Wanli Zhang; Haiyan Gao (Food Chemistry, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

VcMYB30 enhances wax production and maintains fruit quality by regulating cuticular wax biosynthesis genes - Qi Kong; Ruiling Liu; Weijie Wu; Huizhi Chen; Yanchao Han; Xiangjun Fang; Yiqin Zhang; Hangjun Chen; Honglei Mu; Haiyan Gao; Jianye Chen (Postharvest Biology and Technology, 2024)

Inhibitory effect and action mechanism of perillaldehyde on the Fusarium graminearum in postharvest fresh ginger - Xiuling Meng; Weijie Wu; Ben Niu; Ruiling Liu; Huizhi Chen; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2024)

Persistent free radicals generated from a range of biochars and their physiological effects on wheat seedlings - Ruirui Zhang; Andrew R. Zimmerman; Ruiling Zhang; Penghui Li; Yue Zheng; Bin Gao (Science of The Total Environment, 2024)

Development of bio-based PLA/cellulose antibacterial packaging and its application for the storage of shiitake mushroom - Weitao Wang; Ben Niu; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Guannan Wang; Haiyan Gao; Honglei Mu (Food Chemistry, 2023)

Critical taste substances and regulatory pathways of fresh lotus seed pulps at different ripeness stages - Yinai Yang; Ruiling Liu; Yanchao Han; Weijie Wu; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2023)

Melatonin treatment delays the softening of blueberry fruit by modulating cuticular wax metabolism and reducing cell wall degradation - Ruiling Liu; Shang Fanzhen; Ben Niu; Weijie Wu; Yanchao Han; Hangjun Chen; Haiyan Gao (Food Research International, 2023)

Effect of oxyresveratrol on the quality and membrane lipid metabolism of shiitake mushroom (Lentinus edodes) during storage - Ben Niu; Yingchang Fei; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Clogging mechanisms of biological aerobic filter in a petro-chemical wastewater treatment plant: A field study - Xinning Gao; Lixin Zhao; Ruiling Zhang; Shuo Wang; Yanli Pan; Songyan Qin (Journal of Water Process Engineering, 2023)

Ursolic acid, the main component of blueberry cuticular wax, inhibits Botrytis cinerea growth by damaging cell membrane integrity - Ruiling Liu; Liping Zhang; Shangyue Xiao; Hangjun Chen; Yanchao Han; Ben Niu; Weijie Wu; Haiyan Gao (Food Chemistry, 2023)

Applications, impacts, and management of biochar persistent free radicals: A review - Ruirui Zhang; Ruiling Zhang; Andrew R. Zimmerman; Hailong Wang; Bin Gao (Environmental Pollution, 2023)

Extraction of Eucommia ulmoides gum and microbial lipid from Eucommia ulmoides Oliver leaves by dilute acid hydrolysis - Ruiling Gao; Hairong Zhang; Bo Li; Haijun Guo; Hailong Li; Lian Xiong; Xinde Chen (Biotechnology Letters, 2023)

Advances of stable isotope technology in food safety analysis and nutrient metabolism research - Wei Xia; Xiangjun Fang; Yuan Gao; Weijie Wu; Yanchao Han; Ruiling Liu; Hailong Yang; Hangjun Chen; Haiyan Gao (Food Chemistry, 2023)

In vitro fermentation characteristics of the dietary fiber in bamboo (Phyllostachys edulis) shoots and its regulatory effects on the intestinal microbiota and metabolites - Weijie Wu; Qi Li; Hangjun Chen; Xiangjun Fang; Ben Niu; Ruiling Liu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Application of melatonin delays lignification in postharvest water bamboo shoots in association with energy metabolism - Baiqi Yang; Yanchao Han; Haiyan Gao; Ruiling Liu; Feng Xu; Ruihai Liu; Shangyue Xiao; Bin Li; Hangjun Chen (Postharvest Biology and Technology, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

Assessing the mechanism for flood control: a case of plain river network cities under extreme rainfalls - Yihu Wang; Cheng Gao; Jin Xu; Wei Zhang; Liangliang She; Qianqian Zhang; Ruiling Bao (Environmental Science and Pollution Research, 2022)

The Mechanism of Stem Cell Aging - Liangyu Mi; Junping Hu; Na Li; Jinfang Gao; Rongxiu Huo; Xinyue Peng; Na Zhang; Ying Liu; Hanxi Zhao; Ruiling Liu; Liyun Zhang; Ke Xu (Stem Cell Reviews and Reports, 2022)
Stem cells have self-renewal ability and multi-directional differentiation potential. They have tissue repair capabilities and are essential for maintaining the tissue homeostasis. The depletion of stem cells is closely related to the occurrence of body aging and aging-related diseases. Therefore, revealing the molecular mechanisms of stem cell aging will set new directions for the therapeutic application of stem cells, the study of aging mechanisms, and the prevention and treatment of aging-related diseases. This review comprehensively describes the molecular mechanisms related to stem cell aging and provides the basis for further investigations aimed at developing new anti-stem cell aging strategies and promoting the clinical application of stem cells.

A review of risk analysis methods for natural disasters - Ruiling Sun; Ge Gao; Zaiwu Gong; Jie Wu (Natural Hazards, 2020)